Resistance to the Patriarchal Power over Nature and Women in the Novel Tanjung Kemarau by Royyan Julian - Abdul Azis; Wiyatmi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
Tanjung Kemarau is a novel by Royyan Julian about women's resistance to a patriarchal system that exploits nature and women. The method in this research is qualitative descriptive analysis using the perspective of the theory of ecofeminism. The source of the research data consists of the novel Tanjung Kemarau by Royyan Julian. Data is obtained through the reading, identification, and recording of narrative elements in novels containing information about the existence of patriarchal powers and rejecting the exploitation of nature. Research techniques are carried out gradually, ranging from identifying data sources, collecting data, and grouping data. Technical data analysis is done in a way that reduces research data, presents research data, and concludes research data. Based on the research carried out, the results obtained in relation to resistance to patriarchal power over nature and women include: 1) the exploitation of nature; 2) the oppression of women; 3) the preservation of marine trees from exploitation; 4) the conservation of the coastal environment; and 5) the protection of marine life.